2022
DOI: 10.1038/s41419-022-04525-1
|View full text |Cite
|
Sign up to set email alerts
|

E2F transcription factor 2-activated DLEU2 contributes to prostate tumorigenesis by upregulating serum and glucocorticoid-induced protein kinase 1

Abstract: Long noncoding RNAs (lncRNAs) participate in biological processes in multiple types of tumors. However, the regulatory patterns of lncRNAs in prostate cancer remain largely unclear. Here, we evaluated the expression and roles of the lncRNA DLEU2 in prostate cancer. Our results showed that DLEU2 was upregulated in advanced prostate cancer tissues. Patients with prostate cancer displaying high expression of DLEU2 had a poor prognosis. Moreover, we demonstrated that overexpression of DLEU2 facilitated the prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…Moreover, by comparing the differences in the functional enrichment of luminal cells between the TZ and PZ, we found that luminal cells in the PZ expressed higher levels of MYC and E2F target genes, androgen/lineage and DNA repair genes. Excessive activation of the MYC and E2F pathways and their regulated genes have been considered to be an important event in the malignant degeneration of prostate luminal cells, 46 , 47 which may be one of the reasons why luminal cells in the PZ are more susceptible to malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by comparing the differences in the functional enrichment of luminal cells between the TZ and PZ, we found that luminal cells in the PZ expressed higher levels of MYC and E2F target genes, androgen/lineage and DNA repair genes. Excessive activation of the MYC and E2F pathways and their regulated genes have been considered to be an important event in the malignant degeneration of prostate luminal cells, 46 , 47 which may be one of the reasons why luminal cells in the PZ are more susceptible to malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, miR‐582‐5p was reported to repress TGF‐β signaling by directly inhibiting SMAD2 and facilitate NF‐κB pathway by inhibiting CREB, 26,27 both of which might promote inflammation. On the other hand, miR‐582‐5p was also reported to downregulate the expression of HMGB1, EZH2 and SGK1, 28–30 which were previously reported to promote colitis in animal model or clinical samples 31–33 . It is noteworthy that studies mentioned above were all conducted in cancer cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…DLEU2 is the host gene for miR15a/16–1, it regulates B cell proliferation and has been reported to be deleted or epigenetically suppressed in leukemia (Mertens et al, 2006 ; Lerner et al, 2009 ; Klein et al, 2010 ). Previous studies have reported that DLEU2 is expressed in various cell types including immune cells such as B cells and T cells and mainly localized in the cytoplasm (He et al, 2021 , 2; Li et al, 2022 , 2; Dong et al, 2021 ), suggesting that it may have the potential to be translated into protein.…”
Section: Discussionmentioning
confidence: 99%